Factors associated with female genital mutilation among women of reproductive age and girls aged 0-14 in Chad: a mixed-effects multilevel analysis of the 2014-2015 Chad demographic and health survey data - Bright Opoku Ahinkorah (BMC, 2021)
Abstract Background Chad is one of the African countries with high prevalence of female genital mutilation (FGM). The aim of this study was to examine the factors associated with FGM among women aged 15-49 and girls aged 0-14 in Chad. Methods Data for the study were obtained from the 2014-2015 Chad Demographic and Health Survey. FGM among women aged 15-49 and girls aged 0-14 were the outcome variables. The prevalence of FGM among women and girls were presented using percentages while a mixed-effects multilevel multivariable logistic regression analysis was carried out to assess the factors associated with FGM. The results were presented using adjusted odds ratio with associated 95% confidence intervals. Results The results indicate that more than half (50.2%) of the women and 12.9% of girls in Chad had been circumcised. Among women aged 15-49, level of education, employment status, ethnicity, religion, wealth quintile and community literacy level were significant predictors of FGM. Age, partner's level of education, marital status, employment status, ethnicity, religion and mother's FGM status were associated with FGM among girls aged 0-14. Conclusion This study has identified several individual and contextual factors as predictors of FGM among women and girls in Chad. The findings imply the need to adopt strategies aimed at addressing these factors in order to help eliminate the practice of FGM. Government and non-governmental organisations in Chad need to implement policies that enhance media advocacy and community dialogue to help deal with FGM in the country.